O saber ludo-sensível na visão de docentes em um curso de Pedagogia: estudo exploratório na Universidade Estadual do Sudoeste da Bahia - UESB - Sobral, Conceição Maria Alves (2020)
The main purpose of this research is to answer the following questions: a) what is the meaning given to playful-sensitive knowledge in the pedagogical practices of teachers who work in the Pedagogy Course? b) how do teachers constitute playful-sensitive knowledge in their formative itinerancy as university teachers? c) which indicators make up the list of playful-sensitive knowledge and characterize it? The general objective of the research is to analyze the narratives of the teachers of the Pedagogy Course and their vision of playful-sensitive knowledge, describing it and reflecting on the possible manifestations in their pedagogical practice. It is a qualitative research, with an option in phenomenology, adopting as a method the (self) biographical approach (Delory-Momberger 2012; 2014). The studies made are anchored in the researches of the following authors: Tardif (2002); Veiga (2002; 2013); Pimenta e Anastasiou (2012); D'Ávila (2007; 2013; 2014; 2016; 2018); Luckesi (2002; 2007; 2011); Porto (2013); Nóvoa (2002; 2010); Duarte Júnior (2006); Gauthier (2006); Maffesoli (1998). The subjects of the study are six teachers of the Pedagogy Course of the State University of Southwest Bahia, Jequié Campus. The research techniques used are: questionnaire and interview (first phase), and the (self) biographical narratives (second phase) collected at the Biographical Projects Workshop (Delory-Momberger, 2012; 2014). For the treatment and analysis of the data I was inspired by the Content Analysis according to Bardin (2011). The empirical research is presented, in this work, in an articulated way to the theoretical foundation, in an attempt to articulate theory and practice. As main results I have verified that knowledge was felt, constituted during the playful-sensitive formative experience, standing out: the transformation of conception and the vision of pedagogical practice erected by the bias of playfulness and playful-sensitive knowledge, impacted by the experience of autobiographical narratives in the Biographical Workshop of Projects, and professional advancement, besides the significant feelings of affection, joy, pleasure and sharing among the teachers involved in the formative process. I understand that it is not enough just to say that playfulness is a space that allows imagination and creativity. It is necessary to use and believe in the enchantment of teaching and learning coined in the conception of playfulness as an inner experience of full development, integrating reason and emotion, theory and practice, content and form, for example. The thesis that I defend in this research is that ludo-sensitive knowledge is a web knowledge, anchored in the need to reintegrate the sensorial-corporal, emotional, aesthetic and intuitive dimensions to the cognitive dimension, creating bridges between education and organicity in living life - and that extrapolates the school space.